Land Resource Liability Theoretical Analysis and Account Construction. Issue 3 (February 2019) - Han, Dejun; Yuan, Xia; Liu, Jianzhong
Abstract: The purpose is to study the theoretical innovation and account construction of natural resource liability taking land resources as an example. This paper adopts the empirical research method of land resource liability accounting based on the theory of liability. It forms the land resource balance sheet based on "the arable land red line"and "ecological red line". The main conclusions are as follows: (1) Liability accounting for natural resources (including land resources) requires innovation in debt theory; (2) Construction of three - tier structure accounting system for land resources assets and liabilities of the accounting system; (3) The accounting of land resources liabilities must be limited to the "the arable land red line" and "ecological red line", Which improves the third floor of the land resources balance sheet. In practice, The feasibility of land resource liability accounting is also constrained by various factors such as data caliber, land property rights and land valuation.